Selective adsorption of dyes and pharmaceuticals from water by UiO metalâorganic frameworks: A comprehensive review - Zango, Z.U. (Elsevier Ltd, 2021)
Here in, we present a review on the adsorption of dyes and pharmaceuticals from water onto UiO (Universitetet i Oslo) metalâorganic frameworks (MOFs). The MOFs possessed distinctive and promising properties, uncommon to other conventional adsorbents, such as ultra-porosity and remarkable stability, worthy of being super adsorbents for pollutants adsorption from water. They have shown prodigious performance towards the adsorption of both dyes and pharmaceuticals from the aqueous medium at both lower and higher concentrations. The vast adsorption efficiency of the MOFs is heavily attributed to their high Brunauer-Emmett-Teller (BET) surface areas and pore volume, providing abundant adsorption sites for the pollutants. The binding affinity of the MOFs for the dyes and pharmaceuticals adsorption has been elucidated by the different interactions such as electrostatic, hydrogen bonding and Ï-Ï stacking, often dictated by the surface charged of the target pollutant and the zeta potential on the MOF's surface. The MOFs have shown higher efficiency even in multi-component systems. The ease for the regeneration of the MOFs using common organic solvents and the impressive performance for repeated cycles has been outstanding. The MOFs were thus regarded as superior over conventional porous adsorbents and commendable for large scale applications. Â© 2021 Elsevier Ltd